Case Study on the Impact of Permissive Parenting on Early Childhood Social–Emotional Development - Ferawati Ferawati; Brigita Puridawaty; Nova Pujiastuti; Nadyantri Rahmadhani; Fatikha Ni’matussilva; Syarifah Lutfiyah (Kirana Publisher (KNPub), 2026)
Social–emotional development is a critical foundation for children’s lifelong learning, well-being, and social adjustment. Parenting style plays a central role in shaping children’s emotional regulation and social competence during early childhood. This study aims to explore the impact of permissive parenting on early childhood social–emotional development using a qualitative descriptive case study approach. The participant was a six-year-old male child enrolled in an early childhood education institution who demonstrated persistent challenges in emotional regulation. Data were collected through classroom observations, anecdotal records, semi-structured interviews with parents, and documentation. Data trustworthiness was ensured through technique triangulation and source triangulation. Data analysis followed the interactive model proposed by Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings reveal that while the child demonstrated basic social interaction skills and emerging empathy, significant difficulties were evident in emotional regulation, frustration tolerance, and independent problem-solving. These findings suggest that permissive parenting, characterized by high emotional responsiveness and low behavioral control, may limit opportunities for children to develop emotional self-regulation and social–emotional autonomy. This study highlights the importance of balanced parenting practices that integrate warmth with consistent boundaries to support optimal social–emotional development in early childhood.